Managing fruit-borer for having healthy litchi - Srivastava, Kuldeep; Purbey, S K; Patak, R K; Nath, Vishal (Indian Horticulture, 2019)
Litchi (Litchi chinensis) is one of the important subtropical evergreen fruit belonging to family Sapindaceae. India is the second largest producer of litchi in the world after China, with an area and production of 84,000 ha and 594,000 tonnes (2014–15). Many biotic stresses particularly insect pests play a vital role in lowering the quality production and productivity. Under changing climatic condition, litchi fruit and shoot-borer is becoming a major threat to quality litchi production and leading to more than 60% borer infested fruit in unmanaged orchard. Different insect growth regulators (IGRs), avermectins, spinosyns, diamides, bio-enhancers and cultural practices have been found effective against fruit and shoot-borer. Therefore, an attempt has been made to describe litchi fruitand shoot-borer along with probable and advanced management practices to manage this important pest.